Discrimination of infectious hepatitis A virus and rotavirus by combining dyes and surfactants with RT-qPCR - Coudray-Meunier, Coralie (BioMed Central, 2013)
BACKGROUND: Human enteric viruses are major agents of foodborne diseases. Because of the absence of a reliable cell culture method for most of the enteric viruses involved in outbreaks, real-time reverse transcriptase PCR is now widely used for the detection of RNA viruses in food samples. However this approach detects viral nucleic acids of both infectious and non infectious viruses, which limits the impact of conclusions with regard to public health concern. The aim of the study was to develop a method to discriminate between infectious and non-infectious particles of hepatitis A virus (HAV) and two strains of rotavirus (RV) following thermal inactivation by using intercalating dyes combined with RT-qPCR. RESULTS: Once the binding of propidium monoazide (PMA) or ethidium monoazide (EMA) was shown to be effective on the viral ssRNA of HAV and dsRNA of two strains of RV (SA11 and Wa), their use in conjunction with three surfactants (IGEPAL CA-630, Tween 20, Triton X-100) prior to RT-qPCR assays was evaluated to quantify the infectious particles remaining following heat treatment. The most promising conditions were EMA (20 μM) and IGEPAL CA-630 (0.5%) for HAV, EMA (20 μM) for RV (WA) and PMA (50 μM) for RV (SA11). The effectiveness of the pre-treatment RT-qPCR developed for each virus was evaluated with three RT-qPCR assays (A, B, C) during thermal inactivation kinetics (at 37°C, 68 C, 72°C, 80°C) through comparison with data obtained by RT-qPCR and by infectious titration in cell culture. At 37°C, the quantity of virus (RV, HAV) remained constant regardless of the method used. The genomic titers following heat treatment at 68°C to 80°C became similar to the infectious titers only when a pre-treatment RT-qPCR was used. Moreover, the most effective decrease was obtained by RT-qPCR assay A or B for HAV and RT-qPCR assay B or C for RV. CONCLUSIONS: We concluded that effectiveness of the pre-treatment RT-qPCR is influenced by the viral target and by the choice of the RT-qPCR assay. Currently, it would be appropriate to further develop this approach under specific conditions of inactivation for the identification of infectious viruses in food and environmental samples.